An Epistemological Analysis of the Thought of K.H. Syukri Unus and Its Contribution to the Development of Islamic Education - Mukhlis Mukhlis; Fahmi Hamdi; Salamah Salamah; Syaifuddin Sabda; Wahyudin Wahyudin (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study aims to analyze the epistemology of K.H. Syukri Unus’s thought and its contribution to the development of contemporary Islamic education. The focus of the study includes the sources of knowledge, educational objectives, educational methods, the integration of knowledge, and the relevance of his ideas to Islamic education. This research employs a qualitative approach using the library research method. The data were collected through the study of various literary sources, including books, articles, and documents related to the thought of K.H. Syukri Unus and the epistemology of Islamic education. Data analysis was conducted using content analysis with interpretative and philosophical approaches, The findings of the study indicate that the epistemology of K.H. Syukri Unus’s thought is built upon the integration of revelation, reason, and spirituality as the main foundation of Islamic education. He emphasized the importance of character education, exemplary conduct, and the development of socio-religious awareness. The novelty of this research lies in its epistemological analysis of K.H. Syukri Unus’s thought, which has rarely been examined academically, particularly from the perspective of integrating the bayani, burhani, and irfani approaches as a paradigm for the development of contemporary Islamic education